2005
DOI: 10.1183/09031936.05.00083404
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension in advanced sarcoidosis: epidemiology and clinical characteristics: Table. 1—

Abstract: Pulmonary hypertension (PH) is a predictor of poor outcome in sarcoidosis. Little is known about the epidemiology of PH in sarcoidosis.The current authors reviewed the records of patients with sarcoidosis listed for lung transplantation in the USA between January 1995 and December 2002. PH was defined as a mean pulmonary artery pressure of .25 mmHg and severe PH as a mean pulmonary artery pressure of o40 mmHg.The cohort included 363 patients of whom 73.8% had PH. Neither spirometric testing nor the need for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
213
1
16

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(237 citation statements)
references
References 20 publications
7
213
1
16
Order By: Relevance
“…PH ileri evre sarkoidoz olgularında da oldukça sık görülür (25). Bir çalışmada transplantasyon adayı olan 363 skleroderma olgusunda SKK ile PH saptanma oranı %73.8 bulunmuştur (28). İPF olgularında PH prevalansı %32 ile %85 olarak bildirilmektedir.…”
Section: İnterstisyel Akciğer Hastalıkları Ve Pulmoner Hipertansiyonunclassified
“…PH ileri evre sarkoidoz olgularında da oldukça sık görülür (25). Bir çalışmada transplantasyon adayı olan 363 skleroderma olgusunda SKK ile PH saptanma oranı %73.8 bulunmuştur (28). İPF olgularında PH prevalansı %32 ile %85 olarak bildirilmektedir.…”
Section: İnterstisyel Akciğer Hastalıkları Ve Pulmoner Hipertansiyonunclassified
“…(Baughman et al, 2011) The prevalence of SAPH has been reported to be 73.8% in patients being evaluated for lung transplantation, with severe PH (mPAP >40 mm Hg) present in 36% of patients. (Shorr et al, 2005) SAPH is more prevalent in patients with advanced radiographic stage, but can develop in the absence of parenchymal lung abnormalities. In one cohort of 54 patients with sarcoidosis and elevated pulmonary pressures by www.intechopen.com echocardiography, 60% of the patients had radiographic stage IV disease, while 10% had radiologically normal lung parenchyma (stages 0 and I).…”
Section: Epidemiologymentioning
confidence: 99%
“…Interestingly, there was an association with sleeping position as the most involved lung was the dependent one in 94% of the cases. Pulmonary hypertension is not uncommon in ILD and in IPF, sarcoidosis and SSc-ILD it is mainly associated with reduced diffusing capacity of the lung for carbon monoxide and desaturation in exercise, and is a predictor of poor survival [91][92][93][94][95][96][97][98]. Recently, it was proposed that pulmonary vascular resistance measured during right heart catheterisation may predict mortality in ILD [99].…”
Section: Beware Of Comorbiditiesmentioning
confidence: 99%